2020
DOI: 10.1016/j.jconrel.2020.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Novel antibiotic-loaded particles conferring eradication of deep tissue bacterial reservoirs for the treatment of chronic urinary tract infection

Abstract: A significant proportion of urinary tract infection (UTI) patients experience recurrent episodes, due to deep tissue infection and treatment-resistant bacterial reservoirs. Direct bladder instillation of antibiotics has proved disappointing in treating UTI, likely due to the failure of infused antibiotics to penetrate the bladder epithelium and accumulate to high enough levels to kill intracellular bacteria. This work investigates the use of nitrofurantoin loaded poly(lactic-co-glycolic acid) (PLGA) particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Uropathogenic Escherichia coli (UPEC) strains UTI89 49 , CFT073 50 (ATCC 700928), and E. coli 83972 (bei Resources) associated with asymptomatic bacteriuria (ABU) were grown in static Luria-Bertani (LB, Sigma Aldrich) broth at 37°C for 48h to induce expression of type 1 pili. Clinical isolates of Enterococcus faecalis ( E. faecalis 36 [EF36], previously isolated and reported from a patient with chronic UTI 51 , and E. faecalis 77 52 , previously isolated and reported from an asymptomatic healthy male) and Streptococcus agalactiae , previously isolated and reported 52 (Group B Streptococcus), were grown overnight in Tryptone Soya Broth (TSB, Thermo Fisher Scientific) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uropathogenic Escherichia coli (UPEC) strains UTI89 49 , CFT073 50 (ATCC 700928), and E. coli 83972 (bei Resources) associated with asymptomatic bacteriuria (ABU) were grown in static Luria-Bertani (LB, Sigma Aldrich) broth at 37°C for 48h to induce expression of type 1 pili. Clinical isolates of Enterococcus faecalis ( E. faecalis 36 [EF36], previously isolated and reported from a patient with chronic UTI 51 , and E. faecalis 77 52 , previously isolated and reported from an asymptomatic healthy male) and Streptococcus agalactiae , previously isolated and reported 52 (Group B Streptococcus), were grown overnight in Tryptone Soya Broth (TSB, Thermo Fisher Scientific) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…[EF36], previously isolated and reported from a patient with chronic UTI 51 , and E. faecalis 77 52 , previously isolated and reported from an asymptomatic healthy male) and Streptococcus agalactiae, previously isolated and reported 52 (Group B Streptococcus), were grown overnight in Tryptone Soya Broth (TSB, Thermo Fisher Scientific) at 37°C.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…1,[4][5][6][7][8] There are many examples in the literature using PLGA-based materials for delivery of therapeutics to promote either fast or prolonged drug release with applications in cancer treatment, pain management, immunotherapy, and more recently, in the treatment of pulmonary tuberculosis, urinary tract infections, migraine and glaucoma. 5,6,[9][10][11][12][13][14][15] There are several techniques that are used for the preparation of PLGA particles including single and double emulsion solvent evaporation (ESE), nanoprecipitation, spray-drying, microfluidics, and hydrogel templating. 2,[16][17][18][19] These techniques enable the synthesis of a wide range of PLGA nano-and sub-micron sized particles.…”
Section: Introductionmentioning
confidence: 99%
“…Because its operation process is much simpler and easier to control. It is reported that the prepared microspheres by this method are more likely to have large specific surface area, ideal morphology and longer carrier life, which could also expand the application range of microspheres 38–40 . More importantly, electrospraying can easily fabricate the microspheres with different physical shapes by adjusting its conditions, such as porous, hollow, honeycomb, double‐walled structure core‐shell structure and other special‐shaped microspheres, and so forth 9,34,41–44 .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the prepared microspheres by this method are more likely to have large specific surface area, ideal morphology and longer carrier life, which could also expand the application range of microspheres. [38][39][40] More importantly, electrospraying can easily fabricate the microspheres with different physical shapes by adjusting its conditions, such as porous, hollow, honeycomb, double-walled structure core-shell structure and other special-shaped microspheres, and so forth. 9,34,[41][42][43][44] These microspheres can achieve the ability to increase the drug loading efficiency, the protective effect of some drugs, and reaching the purpose of sustained release or even controlled release profiles to avoid adverse reactions caused by the rapid release of some drugs.…”
mentioning
confidence: 99%